About problems of convergence of heat conduction equation solutions for 3D space object - A. N. Chichko; A. S. Borozdin (Литьë и металлургия, 2002)
One of topical problems of mathematical modeling of | thermal processes — numerical solution of thermal conduction equation is examined in the article. There is analyzed the time and spatial step for temperature fields with a complex spatial pattern, containing a lot of elements.